Performance analysis of a new designed PEM fuel cell - Ratlamwala, Tahir Abdul Hussain (2012)
In this paper, a new design for the flow channels is presented, and a parametric study of the proton exchange membrane (PEM) fuel cell is conducted in order to investigate the effect of the new flow channels, as well as different operating parameters, on the efficiency and energy output of the cell. Design parameters are selected based on studies presented in the literature to build a physical and practical model. With the new design of the flow channels, it is noticed that the cell efficiency increases from 33.8% to 47.7% if the temperature of the cell is increased. The power output of the cell increases from 2.6 to 282.5 W when the cell temperature and the current density are increased. Moreover, decrease in the efficiency of the cell ranges from 45.5% to 28.4% with the increase in the current density and membrane thickness. Based on the analytical model, design parameters were selected to manufacture a fuel cell that has a power output of 175 W and an efficiency of 35% running at 353 K and 3 bar, with an effective membrane area of 450 cm2. Experiments are conducted to investigate the effect of newly designed flow channels on pressure distribution. It is found that when hydrogen is supplied from both inlets, pressure across the channels become symmetric and, therefore increasing the power output. This study reveals that, with the proper choice of design parameters, a PEM fuel cell is an attractive economical, efficient, and environmental solution when compared with conventional systems of power generation such as gas turbines. Copyright © 2011 John Wiley & Sons, Ltd.